Effect of aromatic cytokinins and explant position on shoot multiplication of Asparagus offi cinalis L. - Hudák, I.; Magyar-Tábori, K.; Zsombik, L. (International Journal of Horticultural Science, 2013)
Asparagus offi cinalis has been widely studied, but little information is available about its in vitro response to exogenous cytokinin during shoot multiplication. To study the effects of different cytokinins on shoot multiplication of A. offi cinalis ‘Grolim’, in vitro culture was initiated from shoot segments cultured on media with Murashige and Skoog medium. Effects of different aromatic cytokinins (6-benzylaminopurine, 6-benzylaminopurine riboside and meta-topolin) applied in four concentrations (0.5, 1.0, 1.5, 2.0 mg/l) on shoot multiplication of ‘Grolim’ were tested. Effect of explant position (vertically or horizontally) on the shoot multiplication outcome was also studied. Both the length and the number of newly developed shoots were signifi cantly affected by explant position and cytokinin content of the medium. The highest numbers of shoots (4.9) were produced in the presence of 0.5 mg l-1 6-benzylaminopurine riboside when explants were paced horizontally onto the medium. Although the longest shoots (41.5 mm) developed on explants placed vertically onto medium supplemented with 2.0 mg l-1 meta-topolin, the lengths of shoots developed on medium with 0.5 mg l-1 6-benzylaminopurine riboside were also adequate in both explant position (29.5 and 33.6 mm placed horizontally and vertically, respectively).